Women in the mutual societies of Portugal from the end of the nineteenth century to the 1930s - Baptista, V.; Alves, P. M. (Women, work, and activism: Chapters of an inclusive history of labor in the long twentieth century, 2022)
This chapter aims to express recent research on the history of women’s work and activism by focusing on women in the mutual societies of Portugal from a gender perspective. The main objective is thus analysing women’s rights and the discrimination prevailing in mixed associations (including women and men as members). Another central purpose involves recognising women-only associations as a space for meeting and collaboration amongst working-class women and feminists that attained a voice in the mutualism movement in which their claims on welfare issues targeted both themselves and their children. Furthermore, we seek to demonstrate that only in women’s mutual associations did the ideals of democracy and equality, advocated by mutualism, become fulfilled for women. However, in fact, only a few women participated in the mutualism congresses during the First Republic, with some women gaining prominent places in the Assemblies but without any known public interventions according to the sources.